Landing in binary asteroids: A global map of feasible descend opportunities for unpowered spacecraft - Çelik, Onur; Sánchez, Joan-Pau (International Astronautical Federation (IAF), 2017)
Asteroid surface science provides the necessary “ground-truth” to validate and enhance remote sensing from orbiting spacecraft. Yet, due to uncertainties associated with the dynamical environment near asteroids, it is generally prudent for the main spacecraft to remain at a safe distance. Instead, small landers could be used much more daringly. This paper explores the potential for ballistic landing opportunities in binary asteroid systems. The dynamics near a binary asteroid are modelled by means of the Circular Restricted Three Body Problem, which provides a reasonable representation of a standard binary system. Natural landing trajectories are sought that allow for deployment from safe distances and touchdown with minimum local-vertical velocity. The necessary coefficient of restitution to ensure a successful landing and the effects of navigation and deployment errors are also analysed. Assuming deployment errors in the order of 10 meters and 1 cm/s (1-sigma), the results show that ballistic descent landing operations are likely to be successful if targeting near equatorial regions with longitude within 320o to 20o in the secondary of the binary system.
Keywords: Binary asteroid missions; Trajectory design; Ballistic descent trajectories; Circular restricted three body problem; Deployment errors; Covariance matrix